(untitled) (Al-Academy, 2024)
Modern technologies have become a distinct role in the formal structure of the interior space, as they possess several possibilities in building a common aesthetic, perceptual, and semantic structure that enriches the visual image as much as the interpretive capabilities of the recipient. Fashion show spaces are among the interior spaces that require privacy and enrichment of their visual and expressive image within the space. Therefore, it was Dividing the research into four chapters, the first chapter contained the research problem that emerged with the following question: "What are the modern technologies that can be used in interior spaces and are effective in designing fashion show halls?", and the two objectives of the research: "Investing modern technologies and applying them in contemporary interior design." ," "Revealing the reality of the design of the showroom in a local fashion house." The second chapter included the theoretical framework in two sections. The first section dealt with: "Modern technologies and their uses in interior design." The second section dealt with "Designing the interior spaces of fashion houses," and was appended The theoretical framework indicators, and the third chapter came by relying on the descriptive approach in analyzing the samples, as they were analyzed according to the analysis axes form designed according to the literature on the topic and the theoretical framework indicators, and the fourth chapter came with the results and conclusions related to the research topic, and the practical aspect included preparing a design proposal for the local model. The research ends with a list of sources and references